Fuzzy control for yaw tracking of Cormoran AUV - Julián González; Spartacus Gomáriz; Carles Batlle (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This work presents in detail the fuzzy control design for yaw tracking of an autonomous underwater vehicle. This control has been developed from the mathematical description of the hydrodynamic model of the vehicle, which is studied and discussed from different situations both in surge velocity as in changes in yaw reference. The model is linearized and several linear controls are designed for their actuation at certain situations, in a way that the fuzzy control allows to handle those controls globally.